Truly costly search and word-of-mouth communication - Atabek Atayev (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
In markets with search frictions, consumers can acquire information about goods either through costly search or from friends via word-of-mouth (WOM) communication. How do sellers' market power react to a very large increase in the number of consumers' friends with whom they engage in WOM? The answer to the question depends on whether consumers are freely endowed with price information. If acquiring price quotes is costly, equilibrium prices are dispersed and the expected price is higher than the marginal cost of production. This implies that firms retain market power even if price information is disseminated among a very large number of consumers due to technological progress, such as social networking websites.
Keywords: D43; D83; D85; 330; Consumer Search; Word-of-Mouth Communication; Social Networks